1982
DOI: 10.3109/00365528209181041
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing Cholangitis in Ulcerative Colitis

Abstract: In the 5-year period 1974-78, 48 (14%) of 336 patients with ulcerative colitis were found to have hepatobiliary disease. Endoscopic retrograde cholangiography (ERC) was successfully performed in 39 of these 48 patients, and sclerosing cholangitis was demonstrated in 19. One is excluded from this series because Crohn's disease was diagnosed at reclassification of the bowel disease. Two of the 18 patients with ulcerative colitis and sclerosing cholangitis have died, one of cholangiocarcinoma and one of an unrela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2
4

Year Published

1989
1989
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(62 citation statements)
references
References 9 publications
0
56
2
4
Order By: Relevance
“…Interestingly, approximately 80% of patients with PSC have UC in Western countries, [8][9][10] while only 2% to 5% of patients with UC have PSC. 8,[11][12][13] There is a very close relationship of etiology between PSC and UC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, approximately 80% of patients with PSC have UC in Western countries, [8][9][10] while only 2% to 5% of patients with UC have PSC. 8,[11][12][13] There is a very close relationship of etiology between PSC and UC.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong association between PSC and inflammatory bowel disease, particularly ulcerative colitis [3,4]. Approximately 4% of patients with inflammatory bowel disease either have or will develop PSC [5].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have shown that approximately 70 percent of all patients with PSC have coexisting inflammatory bowel disease (IBD). 1,2 In addition, PSC occurs in 2 to 7 percent of patients with ulcerative colitis (UC) [3][4][5][6] and in approximately 1 to 3 percent of patients with Crohn's disease. 7 Patients with PSC have a substantially reduced survival, [8][9][10] caused by progressive fibrosis of the intrahepatic and/or extrahepatic bile ducts, which leads to cirrhosis and eventual liver failure or to the development of cholangiocarcinoma.…”
mentioning
confidence: 99%